Preparations for VR Tactical Training Simulator Efficiency Measurements - Marlok, Tamás; Takács, Márk György (Academic and Applied Research in Military and Public Management Science, 2024)
After investigating the applicability of VR simulators in the Hungarian Defence Forces, we searched further for a specific training location in time and place, where VR tactical simulation can be effectively applied. We hypothesise that the effectiveness of infantry soldier training can be made cheaper and thus more efficient if it is properly thought through. For this purpose, we have prepared a measurement. The scientific background to this measurement is presented in this article, together with an examination of the practical potential of the technology and training. The measurement will be conducted based on this research, experimentally embedded in the training plan of officer candidates.